Electronic pulmonary embolism clinical decision support and effect on yield of computerized tomographic pulmonary angiography: ePE—A pragmatic prospective cohort study. Issue 4 (3rd July 2021) - Bledsoe, Joseph R.; Kelly, Christopher; Stevens, Scott M.; Woller, Scott C.; Haug, Peter; Lloyd, James F.; Allen, Todd L.; Butler, Allison M.; Jacobs, Jason R.; Elliott, C. Gregory
Abstract: Objective: Multiple professional societies recommend pre‐test probability (PTP) assessment prior to imaging in the evaluation of patients with suspected pulmonary embolism (PE), however, PTP testing remains uncommon, with imaging occurring frequently and rates of confirmed PE remaining low. The goal of this study was to assess the impact of a clinical decision support tool embedded into the electronic health record to improve the diagnostic yield of computerized tomography pulmonary angiography (CTPA) in suspected patients with PE in the emergency department (ED). Methods: Between July 24, 2014 and December 31, 2016, 4 hospitals from a healthcare system embedded an optional electronic clinical decision support system to assist in the diagnosis of pulmonary embolism (ePE). This system employs the Pulmonary Embolism Rule‐out Criteria (PERC) and revised Geneva Score (RGS) in series prior to CT imaging. We compared the diagnostic yield of CTPA) among patients for whom the physician opted to use ePE versus the diagnostic yield of CTPA when ePE was not used. Results: During the 2.5‐year study period, 37, 288 adult patients were eligible and included for study evaluation. Of eligible patients, 1949 of 37, 288 (5.2%) were enrolled by activation of the tool. A total of 16, 526 CTPAs were performed system‐wide. When ePE was not engaged, CTPA was positive for PE in 1556 of 15, 546 scans for a positive yield of 10.0%. When ePE was used, CTPA identified PE in 211 of 980 scans (21.5% yield) ( P  < 0.001). Conclusions: ePE significantly increased the diagnostic yield of CTPA without missing 30‐day clinically overt PE.